Imaging of intrarenal haemodynamics and oxygen metabolism. (29th January 2013) - Liss, Per; Cox, Eleanor F; Eckerbom, Per; Francis, Sue T
Summary: The interruption of blood flow results in impaired oxygenation and metabolism. This can lead to electrophysiological changes, functional impairment and symptoms in quick succession. Quantitative measures of organ perfusion, perfusion reserve and tissue oxygenation are crucial to assess normal tissue metabolism and function. Magnetic resonance imaging (MRI) provides a number of quantitative methods to assess physiology in the kidney. Blood oxygenation level‐dependent (BOLD) MRI provides a method for the assessment of oxygenation. Blood flow to the kidney can be assessed using phase contrast MRI. Dynamic contrast‐enhanced MRI and arterial spin labelling (ASL) provide methods to assess tissue perfusion, ASL using the magnetization of endogenous water protons and thus providing a non‐invasive method to assess perfusion. The application of diffusion‐weighted MRI allows molecular motion in the kidney to be measured. Novel techniques can also be used to assess oxygenation in the renal arteries and veins and, combined with flow measures, provide an estimation of oxygen metabolism. Magnetic resonance imaging provides a synergy of non‐invasive techniques to study renal function and the demand for these techniques is likely to be driven by the incentive to avoid the use of contrast media, to avoid radiation and to avoid complications with intervention procedures.